2002
DOI: 10.1515/znb-2002-0103
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Properties and Dimerization Study of Isocyanic Acid

Abstract: Isocyanic Acid, Dimeric Isocyanic Acid Isocyanic acid was prepared in pure form by reaction of KOCN or NaOCN with stearic or oxalic acid in good yield. Identification, characterization and investigation of the thermal stability of HNCO and evidence for a possible existence of "dicyanic acid" have been studied in gas phase, liquid and solid state by vibrational and NMR spectroscopy and mass spectrometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 14 publications
5
43
0
3
Order By: Relevance
“…Thermal decomposition of solid cyanuric acid at 210 • C provides a convenient and relatively clean source of HNCO (Belson and Strachan, 1982), which then diffuses through a capillary (1 mm i.d., 5 cm length) and is mixed with a small flow (50 sccm) of zero air. The system was designed so that the entire capillary was kept at temperature and the gas stream allowed to cool only after mixing to lower concentrations since HNCO is known to polymerize at high concentrations (Fischer et al, 2002). No condensed material was observed in, or downstream of, the mixing volume.…”
Section: Ni-pt-cimsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermal decomposition of solid cyanuric acid at 210 • C provides a convenient and relatively clean source of HNCO (Belson and Strachan, 1982), which then diffuses through a capillary (1 mm i.d., 5 cm length) and is mixed with a small flow (50 sccm) of zero air. The system was designed so that the entire capillary was kept at temperature and the gas stream allowed to cool only after mixing to lower concentrations since HNCO is known to polymerize at high concentrations (Fischer et al, 2002). No condensed material was observed in, or downstream of, the mixing volume.…”
Section: Ni-pt-cimsmentioning
confidence: 99%
“…The NCO − ion could arise either from HOCN, cyanic acid, or HNCO, (isocyanic acid). While cyanate salts, such as sodium cyanate (NaOCN), are known to be stable, they evolve HNCO vapor upon acidification (Fischer et al, 2002), and HNCO has been shown to be the most thermodynamically stable of the possible CHNO isomers (Mladenovic and Lewerenz, 2008). There are several studies of the pyrolysis of biomass, coal, and polyamides, that have unambiguously identified HNCO as a major product by infrared spectroscopy (Hansson et al, 2004;Nelson et al, 1996).…”
Section: Isocyanic Acid (Hnco)mentioning
confidence: 99%
“…5) in aqueous and aqueous-ethanol solutions is possible without catalysis, but proceeds slowly in acidic pH (Aresta et al 2001;Bruno et al 2007;Fischer et al 2002). Consequently, the main ways are the catalytic mechanism described in Eqs.…”
Section: Production Of Ethyl Carbamate In Aqueous and Aqueous-alcoholmentioning
confidence: 99%
“…The reaction of sodium cyanate 3 with an acid (SSA) to produce isocyanic acid 5 could be the first step. 23,37,38 Next, for the generation of the intermediate 7, the proton of SSA is added to isocyanic acid 5 that the proton is perfectly added to nitrogen rather than oxygen. 39 Finally, carbamate 1 is likely to be formed when either alcohol or phenol 2 attack to the carbon of the intermediate 7 (Scheme 3).…”
Section: C-nmr (125 Mhz) the Signals Of Carbonyl Carbon Of Aliphatic Ormentioning
confidence: 99%